The Political Structure of UK Broadcasting 1949 - 1999 - Elstein, David (Media, Democracy & Political Process, 2015)
In 1999 David Elstein delivered a lecture series examining the evolvement of UK Broadcasting policy from 1949 to 1999. His sharp analysis is a valuable contribution to the post-war development of the British broadcasting system and unfolds many topical issues in current media policy debates.